Novel thermoelectric performance of 2D 1T- Se2Te and SeTe2 with ultralow lattice thermal conductivity but high carrier mobility. (19th August 2021) - Chen, ShaoBo; Tao, Wang-Li; Zhou, Yu; Zeng, Zhao-Yi; Chen, Xiang-Rong; Geng, Hua-Yun
Abstract: The design and search for efficient thermoelectric materials that can directly convert waste heat into electricity have been of great interest in recent years since they have practical applications in overcoming the challenges of global warming and the energy crisis. In this work, two new two-dimensional 1T-phase group-VI binary compounds Se2 Te and SeTe2 with outstanding thermoelectric performances are predicted using first-principles calculations combined with Boltzmann transport theory. The dynamic stability is confirmed based on phonon dispersion. It is found that the spin–orbit coupling effect has a significant impact on the band structure of SeTe2, and induces a transformation from indirect to direct band gap. The electronic and phononic transport properties of the Se2 Te and SeTe2 monolayer are calculated and discussed. High carrier mobility (up to 3744.321 and 2295.413 cm 2 V −1 S −1 for electron and hole, respectively) is exhibited, suggesting great applications in nanoelectronic devices. Furthermore, the maximum thermoelectric figure of merit zT of SeTe2 for n-type and p-type is 2.88, 1.99 and 5.94, 3.60 at 300 K and 600 K, respectively, which is larger than that of most reported 2D thermoelectric materials. The surprising thermoelectric properties arise from the ultralow lattice thermal conductivity k l (0.25 and 1.89 W m −1 K −1 for SeTe2 and Se2 Te at 300 K), and the origin of ultralow lattice thermal conductivity is revealed. The present results suggest that 1T-phase Se2 Te and SeTe2 monolayer are promising candidates for thermoelectric applications.